Synthesis and evaluation of Re/99mTc(I) complexes bearing a somatostatin receptor-targeting antagonist and labeled via a novel [N, S, O] clickable bifunctional chelating agent. Issue 3 (1st February 2019) - Radford, Lauren L.; Papagiannopoulou, Dionysia; Gallazzi, Fabio; Berendzen, Ashley; Watkinson, Lisa; Carmack, Terry; Lewis, Michael R.; Jurisson, Silvia S.; Hennkens, Heather M.
Graphical abstract: Abstract: The somatostatin receptor subtype 2 (SSTR2) is often highly expressed on neuroendocrine tumors (NETs), making it a popular in vivo target for diagnostic and therapeutic approaches aimed toward management of NETs. In this work, an antagonist peptide (sst2 -ANT) with high affinity for SSTR2 was modified at the N -terminus with a novel [N, S, O] bifunctional chelator (2 ) designed for tridentate chelation of rhenium(I) and technetium(I) tricarbonyl cores, [Re(CO)3 ] + and [ 99m Tc][Tc(CO)3 ] + . The chelator-peptide conjugation was performed via a Cu(I)-assisted click reaction of the alkyne-bearing chelator (2 ) with an azide-functionalized sst2 -ANT peptide (3 ), to yield NSO-sst2 -ANT (4 ). Two synthetic methods were used to prepare Re-4 at the macroscopic scale, which differed based on the relative timing of the click conjugation to the [Re(CO)3 ] + complexation by2 . The resulting products demonstrated the expected molecular mass and nanomolar in vitro SSTR2 affinity (IC50 values under 30 nM, AR42J cells, [ 125 I]iodo-Tyr 11 -somatostatin-14 radioligand standard). However, a difference in their HPLC retention times suggested a difference in metal coordination modes, which was attributed to a competing N -triazole donor ligand formed during click conjugation. Surprisingly, the radiotracer scale reaction of [ 99m Tc][Tc(OH2 )3 (CO)3 ] + ( 99m Tc; t½  = 6 h, 141 keV γ) with4 formed a third product, distinct from the Re analogues, making this one of the unusual cases in which Re and Tc chemistries are not well matched. Nevertheless, the [ 99m Tc]Tc-4 product demonstrated excellent in vitro stability to challenges by cysteine and histidine (≥98% intact through 24 h), along with 75% stability in mouse serum through 4 h. In vivo biodistribution and microSPECT/CT imaging studies performed in AR42J tumor-bearing mice revealed improved clearance of this radiotracer in comparison to a similar [ 99m Tc][Tc(CO)3 ]-labeled sst2 -ANT derivative previously studied. Yet despite having adequate tumor uptake at 1 h (4.9% ID/g), tumor uptake was not blocked by co-administration of a receptor-saturating dose of SS-14. Aimed toward realignment of the Re and Tc product structures, future efforts should include distancing the alkyne group from the intended donor atoms of the chelator, to reduce the coordination options available to the [M(CO)3 ] + core (M = Re, 99m Tc) by disfavoring involvement of the N -triazole.